Cytomegalovirus infection in pregnancy Die schwangerschaftsassoziierte CMV-Infektion: praktisches Vorgehen - Meyer-Wittkopf, Matthias; Faschingbauer, Florian (gynäkologische praxis, 2021)
In 0.5–4 % of all pregnancies, the seronegative future mother will be affected by a primary cytomegalovirus (CMV) infection during her pregnancy. If the developing embryo/ fetus is infected during the periconceptional or first trimester period, serious teratogenic long-term impairment of the fetal brain including mental retardation, cerebral palsy, epilepsy, or progressive hearing loss may result. 85–90 % of all neonates with a prenatally acquired CMV infection are asymptomatic at birth. Periconceptional hygienic counselling measures can reduce the risk of primary CMV infection during pregnancy by 50–85 %. National and international studies with an anti-CMV-specific hyperimmunoglobulin (HIG) preparation found a time interval and study design dependent reduced rate of both vertical virus transmission and serious infectious sequelae in offspring of mothers with a primary seroconversion during pregnancy. However, only few of these study protocols reached statistical significance. Another off-label treatment option in cases with proven or possible fetal CMV infection is the antiviral therapy with virostatics after maternal seroconversion during the first trimester. Except for study purposes any active vaccination against CMV is currently still unavailable. Thus, periconceptional counselling of seronegative future mothers still remains the most effective way to prevent teratogenic CMV infection during pregnancy.
CRIS-Team Scopus Importer:2024-12-16
Keywords: cytomegalovirus; pregnancy; prevention; teratogenicity; therapy